Amplifying user experience on virtual reality through level design based on environmental storytelling - SOUZA NETO, Arlindo Gomes de (2022)
In virtual reality (VR) applications, the number of games that feature complex narratives is still low compared to traditional games; according to Steam data, they are only 4 of the 15 best-selling VR games. We can attribute this fact to the high cost of developing these experiences as they require a lot of testing, research, and experience from the development team. One of the approaches that help teams tell stories is environmental storytelling, which consists of telling stories through the environment to collaborate with the overall narrative being told. Previous work has already demonstrated the effectiveness of environmental storytelling in digital games. However, there is little material relating this approach to VR, a technology notably known for promoting spatiality, immersion, and presence in virtual environments and which could benefit from a refined approach to environmental storytelling. In this work, we propose a classification framework for environmental storytelling approaches and assess the impact of these strategies in a test with 12 players of different gamer types; the experiment consists of users playing four specific segments of a VR commercial game that presents approaches and strategies of environmental storytelling. We conclude that the type of players impacts their reaction to environmental storytelling approaches and strategies. Also, the authors observed behavior patterns throughout the experiments, but further research needs to be done in larger groups to generalize those behavior patterns.